Combination of monoclonal antibody (Bevacizumab) and chemotherapy (FOLFIRI) in palliative treatment of metastatic adenocarcinoma of the small bowel (SBC): case report and review of the literature. - Stec, Rafał; Grala, Bartłomiej; Mączewski, Michał; Bodnar, Lubomir; Zegadło, Arkadiusz; Szczylik, Cezary (Archives of Medical Science, 2009)
Small bowel cancer (SBC) is very rare malignancy. Annually about only 89 new cases of SBC are diagnosed in Poland (0.1-0.3%) of all malignancies and approximately 1% of gastrointestinal cancers. The prognosis of metastatic SBC is rather poor. The median survival of patients undergoing chemotherapy is approximately 14 months. Small bowel cancer is considered refractory to chemotherapy. Various anticancer agents have been tested in palliative chemotherapy of SBC: 5-Fluorouracil (5-FU), Cisplatin, Adriamycin, Mitomycin C, Oxaliplatin, Irinotecan, Carboplatin. Here we report a rare case of metastatic SBC with complete response (CR) after combination treatment with monoclonal antibody (Bevacizumab) and FOLFIRI (5-FU, Leukovorin, Irinotecan). The patient is alive without disease progression 28 months after her primary presentation of SBC.